(untitled) (Journal of Educational Sciences, 2023)
The article deals with a student-oriented chatbot used in the educational process. Chatbots are used in various fields, including education. Thus, new opportunities open up for teachers to establish quick contact with students and transfer information. Educational chatbots are being developed for pedagogical purposes and are seen as an interface that could revolutionize teaching and learning. Chatbots such as educational chatbots are designed to provide student-centered learning through the concept of a virtual assistant that reproduces a human conversation. However, in the educational paradigm, chatbots are still an innovation in developing and integrating them as an effective pedagogical tool in many areas. The research aims to add to the existing knowledge about the development of chatbots a new strategy, pedagogical and practical implications. Educational chatbots can evaluate interactions with students. It also makes it much easier for students to learn more about courses, lectures and create a better learning environment. Student-centered chatbots have a consistent personality, they provide more informative answers and further act as personal assistants. Existing student-centered approaches include several textual descriptions as explicit user profiles. In this article, we propose to study user dialogues to create student-oriented chatbots. In particular, by taking advantage of the chatbot for understanding the subject being studied, we train a student-centered model to create a general user profile. In order to explicitly use student frequently asked questions, we are developing a student-centric personalized user. In addition, the article defines the functions and areas of use in the educational environment. A comparative analysis of the platforms and their potential for the implementation of chatbots was also carried out. With the help of the ManyBot constructor, a chat bot "Virtual Assistant for DL" was created for implementation in the educational process and integrated into the Telegram messenger and browser. A survey was conducted among teachers, students, undergraduates and doctoral students. The results of the survey showed the relevance of using chatbots in education. Key words: personalized approach, student-centered approach, individuality, learning process, artificial intelligence, chatbot, virtual assistants, education.